2016
DOI: 10.1590/s01518-8787.2016050006698
|View full text |Cite
|
Sign up to set email alerts
|

ERICA: intake of macro and micronutrients of Brazilian adolescents

Abstract: OBJECTIVE To describe food and macronutrient intake profile and estimate the prevalence of inadequate micronutrient intake of Brazilian adolescents.METHODS Data from 71,791 adolescents aged from 12 to 17 years were evaluated in the 2013-2014 Brazilian Study of Cardiovascular Risks in Adolescents (ERICA). Food intake was estimated using 24-hour dietary recall (24-HDR). A second 24-HDR was collected in a subsample of the adolescents to estimate within-person variability and calculate the usual individual intake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
91
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 18 publications
14
91
1
12
Order By: Relevance
“…Results from the Brazilian Study of Cardiovascular Risks in Adolescents (ERICA) were similar to those found in the present study. The estimates in ERICA for the mean contribution of macronutrients (as a % of TE intake) from protein (15.4 and 16.3%), carbohydrate (54.0 and 53.7%), total fat (30.9 and 30.2%) and saturated fat (11.3 and 10.8%) among females and males aged 14-17 years, respectively, were close to our results [41].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results from the Brazilian Study of Cardiovascular Risks in Adolescents (ERICA) were similar to those found in the present study. The estimates in ERICA for the mean contribution of macronutrients (as a % of TE intake) from protein (15.4 and 16.3%), carbohydrate (54.0 and 53.7%), total fat (30.9 and 30.2%) and saturated fat (11.3 and 10.8%) among females and males aged 14-17 years, respectively, were close to our results [41].…”
Section: Discussionsupporting
confidence: 88%
“…The high saturated fat intake confirmed by our study should be highlighted, as we can see on a global scale that American, Latin American and European adolescent populations have a high percentage of total energy intake that comes from this nutrient [38,39,41]. According to the FAO and the WHO, saturated fat should provide a maximum of 10% of total energy intake; but, in the present study, higher energy intake from this nutrient was reported by 46.8% of adolescents.…”
Section: Discussionsupporting
confidence: 53%
“…Data from a national survey in 2014 showed that one out of four Brazilian adolescents had excess weight and 8.4% were already obese 4 . Meanwhile, adolescents' dietary habits have been characterized by high consumption of ultra-processed foods, high in fats, sugars, and sodium, and low consumption of fruits and vegetables 5,6,7 . Factors contributing to this scenario include the familiar environment, which plays an important role in the development of eating habits in children and adolescents 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Soft drinks are among the liquid foods most widely ingested by children and adolescents in Brazil [12]. Studies have shown that regular soft drinks are the second beverage most widely consumed during the meal by adolescents (28.6%) [13].…”
Section: Introductionmentioning
confidence: 99%